DESIGN OF A MANIPULATOR OF A CONVEYOR FOR BULK MATERIALS – CALCULATION OF THE CENTER OF GRAVITY OF THE CONVEYOR - Miroslav BLATNICKÝ; Ján DIŽO; Denis MOLNÁR; Paweł DROŹDZIEL (Scientific Journal of Silesian University of Technology. Series Transport)
The predominant goal of the research presented in this paper is the design of a manipulator for a conveyor of bulk materials based on the given requirements. This issue is an emerging topical one mainly for the reasons of increasing efficiency and speed, as well as the safety of maintenance of machines and equipment. Especially, another essential aspect is the reduction of the physical strain on operators during service operations on the conveyor of bulk materials. The introductory part of this paper attends to the materials used for the production of steel structures, their technological processing, as well as different types of joining of their components. The practical part was set out to ascertain the mass and position of the center of gravity of the load itself – the conveyor. From the perspective of acting, it loads the entire proposed structure, although in different operating modes.